Effectiveness of Nearpod Learning Media to Increase Student Participation - oky fathama rahmania; Minsih Minsih (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2024)
This study aims to examine the effectiveness of Nearpod media in increasing student participation. The method used is quantitative with a pre-experiment design, specifically the One Group Pretest-Posttest design. The sampling technique used the Slovin formula, with a sample size of 23 students from class 3B SDN Kandangan 1 Ngawi. This research was conducted for about 3 weeks, with data collection through two ways: first, giving a pre-test in the form of a questionnaire before treatment, and second, giving a post-test after treatment. Data were analysed using normality test and T-test. The results showed a change in the use of Nearpod media to increase student participation, as evidenced by the test results that HO was rejected and Ha was accepted, because the value of Sig. (2-tailed) of 0.000 <0.05. Thus, it can be concluded that the use of Nearpod media successfully increases student participation.